2022
DOI: 10.1182/blood.2022015522
|View full text |Cite
|
Sign up to set email alerts
|

Immune landscape after allo-HSCT: TIGIT- and CD161-expressing CD4 T cells are associated with subsequent leukemia relapse

Abstract: Allogeneic hematopoietic stem-cell transplantation (allo-HSCT) is the most effective treatment for selected patients with acute myeloid leukemia (AML) and relies on a "graft-versus-leukemia" effect (GVL) where donor T lymphocytes mediate control of malignant cell growth. However, relapse remains the major cause of death after allo-HSCT. In various malignancies, several immunoregulatory mechanisms have been shown to restrain antitumor immunity, including ligand-mediated engagement of inhibitory receptors on eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 59 publications
(71 reference statements)
1
18
0
Order By: Relevance
“…By immune infiltration analysis, we found that the high-risk group showed higher immune scores, but increased ratio of gamma delta T cells, M2 macrophages, MDSCs and Tregs and increased expression of CTLA4 and IL2RA. In many cancers, immunoregulatory mechanisms have been proved to hamper antitumor immunotherapy, including ligand-mediated engagement of IRs on effector cells, such as CTLA4, and induction of immunosuppressive cell subsets, such as Tregs or MDSCs ( 78 80 ). IL2RA was demonstrated to be involved in inferior outcomes of AML patients ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…By immune infiltration analysis, we found that the high-risk group showed higher immune scores, but increased ratio of gamma delta T cells, M2 macrophages, MDSCs and Tregs and increased expression of CTLA4 and IL2RA. In many cancers, immunoregulatory mechanisms have been proved to hamper antitumor immunotherapy, including ligand-mediated engagement of IRs on effector cells, such as CTLA4, and induction of immunosuppressive cell subsets, such as Tregs or MDSCs ( 78 80 ). IL2RA was demonstrated to be involved in inferior outcomes of AML patients ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…27 TIGITmediated immune escape as a mechanism of post-HCT AML relapse was suspected as the TIGIT ligand is expressed on AML blasts, and the expression density was increased in post-HCT relapse samples. 27 Like clinical studies using anti-PD-1 and anti-CTLA-4 immunotherapy, further development using immune receptors and their ICM targets mentioned above are limited by concerns for GVHD exacerbation, and careful development to select responses on tumour without targeting healthy tissue by the alloreactive T-cells remains crucial. [27][28][29] Albeit less common altered expression in other immunerelated genes are implicated in post-HCT relapse.…”
Section: Alterations In Icmsmentioning
confidence: 99%
“…27 Like clinical studies using anti-PD-1 and anti-CTLA-4 immunotherapy, further development using immune receptors and their ICM targets mentioned above are limited by concerns for GVHD exacerbation, and careful development to select responses on tumour without targeting healthy tissue by the alloreactive T-cells remains crucial. [27][28][29] Albeit less common altered expression in other immunerelated genes are implicated in post-HCT relapse. More commonly observed was significantly altered expression of immune-related genes post-HCT compared to diagnostic samples.…”
Section: Alterations In Icmsmentioning
confidence: 99%
“…Immune reconstitution after HSCT is dominated by homeostatic peripheral expansion of the graft-derived cells during the initial stages post-transplantation ( 11 , 12 ). Differences in the immune reconstitution are expected between UCBT and PBSCT because they represent two diverse sources of HSCs and progenitor cells.…”
Section: Introductionmentioning
confidence: 99%